Creating genetic reference datasets: Indirect sampling of target species using terrestrial leeches as sample "collectors". Issue 2 (27th September 2021) - Wilting, Andreas; Nguyen, Thanh V.; Axtner, Jan; Nguyen, An; Schmidt, Anke; Le, Minh; Nguyen, Anh H. Q.; Rawson, Benjamin M.; Tilker, Andrew; Fickel, Joerns
Abstract: Sampling genetic material from rare and often secretive mammals can be difficult in challenging environments such as tropical rainforests. Large‐scale sampling is important however for resolving species' taxonomic uncertainties, as well as to help provide genetic material for reference databases that can be used with DNA forensics to combat the illegal wildlife trade. Environmental DNA (eDNA) and invertebrate‐derived DNA (iDNA) offer a promising way to overcome this sampling bottleneck, though to date e/iDNA studies have been primarily used to obtain information about species presence using barcoding or metabarcoding approaches. In this study, we collected 4, 710 terrestrial leeches across six protected areas in the Annamite Mountains of Viet Nam and Laos and sequenced fragments (223–694 bp) of mt ‐ Cytb and/or mt ‐ Dcr of the mitogenomes from six species that are frequently found in the illegal wildlife trade. Although amplification success was generally low (<50%) because DNA was highly degraded, we showed that e/iDNA samples can be an important source of genetic material for difficult to sample species and show promise as a way to fill existing sampling gaps. Because e/iDNA sampling has the potential to generate much‐needed genetic data to improve taxonomic assessments, this approach can be used to support conservation management by contributing to genetic databases that are necessary to determine the origin of wildlife products or to inform the reintroduction of confiscated animals. Abstract : Sampling genetic material from rare and often secretive mammals is challenging, due to logistical and ethical problems associated with collecting wildlife samples directly. We used terrestrial leeches collected across multiple protected areas in the Annamite Mountains as non‐invasive sample collectors to fill geographic sampling gaps for three carnivore and three ungulate species. We show that iDNA sampling can support conservation management by enhancing the genetic databases that are necessary to determine the origin of wildlife products or help reintroduction programs as confiscated animals can be released back to their original population.